(untitled) (Swiss Medical Weekly, 2019)
The war on cancer remains a major challenge. One of the obstacles to additional progress is the complexity of the mechanisms underlying the disease. Cutting-edge technologies and computing tools have led to whole genome sequencing and an integrated and inclusive omic approach to cancers, from accurate molecular signatures of tumours to impressive progress in the field of next-generation sequencing (NGS). Genomic data may foster strategies for new drug development in addition to a better understanding of cancer genesis, opening a new era in oncological clinical practice. This review discusses the development of genomics approaches in cancer research and the potential of genomics for precision medicine, as well as clinical implications and remaining challenges.